INFLUENCE OF COSTUMER LOYALTY ON FAST FOOD RESTAURANTS IN BATAM - Kiki Nadila; Golan Hasan (Universitas Internasional Batam, 2022)
This day and age, there are many people who spend more. A lot of money for fast food compared to buying a vehicle, Books, laptops, clothes and more. There are a lot of fast food restaurants. Popping up everywhere and the more the times are growing in support it with fast food restaurant facilities that are very helpful and facilitate bookings such as for example people can do booking via mobile phone there can be a direct phone to order or You can also go through applications such as gofood, grabfood and others. As you can see, especially in Batam, Indonesia. There's been a lot once a fast food restaurant that enters Batam that is no stranger to the people in Batam. Like, KFC (Kentucy Fried Chicken), McDonald's, A&W, Rechesse and Burger King. With so many fast food restaurants. in this batam city, so there are also various types of services that can be given to his customers. This study was conducted to analyze the factors that affect Costumer Loyalty to Fast Food Restaurants in Batam City. The dependent variable is Costumer Loyalty while independent variables consist of, Service, Qualtiy, Brand Image and Price that affect the intervening variable is trust.